DOI: 10.11606/d.25.2015.tde-03062015-084513
|View full text |Cite
|
Sign up to set email alerts
|

Estágios motivacionais e sua correlação com sintomas de ansiedade e depressão em pacientes com disfonia

Abstract: À minha mãe, Raimunda da Silva Coelho exemplo de resiliência, incentivando-me a buscar meus sonhos mesmo de coração partido pela minha ausência. Ao meu pai, Alcivando Brito Costa, por suas palavras fortes e protetoras, que me ampararam nas dificuldades da caminhada. AGRADECIMENTOS À Deus por a cada instante dar provas da sua presença e amor incomparável a está pequenina criatura, que sem Ele nada é bom. "Confiar em Deus significa: crer que tudo o que acontece é o melhor" (W. Goes) Aos Meus irmãos especialmente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
1

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 59 publications
1
5
0
1
Order By: Relevance
“…There was no significant difference between the other scores of VAPP and adherence scale (Table 5). (10,16) have used URICA-VOICE scale to evaluate adherence of vocal therapy and found that most patients were in the contemplation stage, followed by pre-contemplation and action. The sample of the studies was made up of patients in speech therapy with behavioral dysphonia and no behavioral dysphonia (10) , as well as behavioral patients in healthcare, discharged and on waiting list (16) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There was no significant difference between the other scores of VAPP and adherence scale (Table 5). (10,16) have used URICA-VOICE scale to evaluate adherence of vocal therapy and found that most patients were in the contemplation stage, followed by pre-contemplation and action. The sample of the studies was made up of patients in speech therapy with behavioral dysphonia and no behavioral dysphonia (10) , as well as behavioral patients in healthcare, discharged and on waiting list (16) .…”
Section: Resultsmentioning
confidence: 99%
“…(10,16) have used URICA-VOICE scale to evaluate adherence of vocal therapy and found that most patients were in the contemplation stage, followed by pre-contemplation and action. The sample of the studies was made up of patients in speech therapy with behavioral dysphonia and no behavioral dysphonia (10) , as well as behavioral patients in healthcare, discharged and on waiting list (16) . An intervention research with six speech therapy sessions, found most of the subjects with behavioral dysphonia in the contemplation stage and an increase in the percentage of action of the post-therapy (3).…”
Section: Resultsmentioning
confidence: 99%
“…Auditory-perceptual and acoustic analyses of the voice were performed before and after speech therapy to measure the results of this intervention. In addition to these assessments, the Voice Handicap Index (VHI-10) protocol was used (7) pre-and post-speech therapy to identify the voice impairments of teachers and the University of Rhode Island Change Assessment URICA-VOICE scale (9) was applied in the fourth session to identify the stages of motivation regarding vocal change. Self-perception of the teachers was verified by the question "How do you evaluate your voice?…”
Section: Methodsmentioning
confidence: 99%
“…After calculating the means of each stage, the following formula is employed: (Average of C + Average of A + Average of M) -Average of PC. Classification in stages depends on the numeric scores described ahead: ≤8 for individuals in the pre-contemplation stage; 8-11, for individuals in the contemplation stage; 11-14, for individuals who are prepared for an attitude of action before the problem (9) .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation